INCOME GENERATION NEEDS TO BE A PRIORITY FOR UNIVERSITIES’ HOLDING COMPANIES - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
BUKIT JAMBUL,PENANG, 2 June 2016 – It is a must for Public Higher Education Institution (IPTA) Holding companies to go into business and commercialisation, said the ViceChancellor of Universiti Sains Malaysia (USM), Professor Dato’ Dr. Omar Osman in his presentation at the Majlis Syarikat Induk IPTA Malaysia (MSIM) Seminar 2016 here today.